MiR-22 inhibits myocardial fibrosis in rats with myocardial infarction by targeting PTEN/Akt/mTOR signaling pathway: MiR-22 in rats with myocardial infarction - Li, Bolin; Liang, Chunna; Lv, Yuanjun; Tan, Yongjin; Chen, Weiyan (Cellular and Molecular Biology, 2024)
This study aimed to evaluate the effects of miR-22 on myocardial fibrosis in rats with myocardial infarction (MI) and to further explore the possible underlying mechanism. A total of 80 rats were randomly divided into Sham group, miR-22 overexpression group, MI group or MI + miR-22 overexpression group. Reverse transcription-polymerase chain reaction (RT-PCR) results showed that compared with Sham group, miR-22 expression level in myocardial tissues of rats decreased significantly in MI group. Overexpression of miR-22 could remarkably relieve cardiac insufficiency in MI rats, increase EF% and FS%, and reduce collagen deposition and the mRNA expression level of fibrosis-promoting genes in myocardial tissues of MI rats. The cross-sectional area of myocardial cells in MI + miR-22 mimic group was smaller than that in MI group. According to the results of immunohistochemical staining, overexpression of miR-22 notably reduced the level of oxidative stress marker 4-HNE in myocardial tissues of MI rats. Meanwhile, myocardial cells in MI + miR-22 mimic group exhibited a prominently lower apoptosis rate than those in MI group. Furthermore, Western blotting results demonstrated that overexpression of miR-22 inhibited the activation of the phosphatase and tensin homolog deleted on chromosome ten (PTEN)/Akt/mTOR signaling pathway in myocardial tissues of MI rats. The inhibitory effects of miR-22 on myocardial fibrosis and hypertrophy after MI in rats may be related to its inhibition on the PTEN/Akt/mTOR signaling pathway. All our findings suggested that miR-22 is expected to become a targeted drug for the clinical treatment of MI.